ANEMIA DURING PREGNANCY IN THE WOMEN OF WESTERN NEPAL - Singh, P; Khan, and, S; Mittal, R. K (BALI MEDICAL JOURNAL; Volume 2 Number 1, January-April 2013, 2013)
Objective: Anemia is the most common nutritional deficiency disorder in the world. The prevalence of anemia in pregnancy varies considerably because of differences in socioeconomic conditions, lifestyles and health seeking behaviors across different cultures. The aim of this study was to evaluate the prevalence of anemia among pregnant women in western part of Nepal. Method : A hospital based study was carried out in Nepalgunj Medical College, Kohalpur, Banke Nepal to determine prevalence of anemia among pregnant women. A total of 512 pregnant (15-45 years old) were included in this study. Cyanmethaemoglobin method was used to determine the hemoglobin level. The study took place from January 2012 to December 2012. Statistical analyses were carried out by applying percentage and words excel 2007. Results : Out of five hundred twelve pregnant women, 210 (41.02%) pregnant women were anemic and 302 pregnant women were non anemic (58.98%). Also, among these anemic pregnant women, majority (67.14 %) of these women were mildly anemic, whereas 28.57% were moderately and 4.29% were severely anemic . Conclusion: Prevalence of anemia was higher in the pregnant women at the second trimester (51.1%) and also at the 20-35 years age group (62.79%).
Keywords: Pregnancy, Anemia, Prevalence, Hb concentration